Pengaruh Pendidikan Kesehatan Melalui Video Animasi Terhadap Pengetahuan ASI Eksklusif Pada Ibu Primigravida: The Effect of Health Education Through Animation Videos on Knowledge of Exclusive Breastfeeding in Primigravida Mothers - Fauziah, Siti Laros; Tridiyawati, Feva (Indonesian Scholar Journal of Nursing and Midwifery Science, 2023)
Introduction: Based on research by the Indonesian Pediatrician Association (IDAI) the number of mothers who have breastfed their children in Indonesia is already high, namely 90% but those who provide exclusively for 6 months are still low at 20%. Breastfeeding is recommended for up to two years. From the preliminary study that the researchers conducted, the knowledge of primigravida mothers in the Carita Health Center area was still lacking. The percentage of exclusive breastfeeding for babies 0-6 months in the Carita Health Center area was still low at 65%.  Methods: This method uses an experimental method, a pre-experimental design in the form one group pre-test-post-test design. The sample in this study were primigravida mothers in the working area of the Carita Public Health Center, Pandeglang Regency, totaling 46 people. The sampling technique used in this research is total sampling. The research instrument used a questionnaire. Bivariate analysis using paired t-test.  Results: Primigravida mothers' knowledge about exclusive breastfeeding before being given intervention in the Carita Health Center area most of them had less knowledge namely as many as 24 respondents (52,2%). After being given the intervention, most of them had sufficient knowledge namely as many as 26 respondents (56,5%). The results of the paired t-test showed that before and after giving health education through animated video media, the p-value was 0,000 (<0,05).  Discussion: There is an effect of health education through animated videos on knowledge of exclusive breastfeeding in primigravida mothers in the Carita Health Center area.